ANALYSIS OF DAMAGE LEVEL AND COST ESTIMATION OF THE SAMUDRAJAYA 04 BEKASI STATE ELEMENTARY SCHOOL BUILDING - Anisah Anisah; Lenggogeni Lenggogeni; Sri Langsih Agustina (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
This study aims to determine the level of damage to the school building using a benchmark assessment of the level of damage by DG Pauddikdasmen Kemendikbud in 2021 and investigate the building component repair-cost estimates using Works Unit Price Analysis (AHSP). The research population is a public elementary school in Samudrajaya Village with a sample building SDN Samudrajaya 04 Bekasi as the object of research. The method used in this research is a descriptive research method with a quantitative approach. The data collection technique was carried out through observation, documentation, and unstructured interviews. The results showed that the level of damage to the SDN Samudrajaya 04 Bekasi building in building one was slightly damaged, with the highest component of damage found in the wall component with brick wall sub-components or partition 8.2% glass, doors, and frames were not damaged. While the level of damage to building two was heavily damaged, with the highest component damage found in the wall components of the sub-components of brick or partition walls by 15%, glass 90.3%, doors 88.6%, and frames 96%. The results of the analysis of the estimated repair costs on the components that experienced the most serious damage based on the volume of damage were in building one of Rp. 30,522,168,48 and in building 2 Rp. 204,070,178.35, the total repair cost is Rp. 234,592,346.83 or can be rounded up to Rp. 234,593,000.